HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN DENGAN KUALITAS MIKROBIOLOGI AIR SUMUR BOR YANG DIGUNAKAN MASYARAKAT SEKITAR TPA TANJUNG PINGGIR KOTA PEMATANGSIANTAR - Ulhaq, Arifqah Dhiya; Azizah, R; Pangidoan, Yoel Sahat; Timantha, Leo Eykel (VISIKES, 2025)
Clean water is one of the primary needs for human survival to continue. The quality, quantity and continuity of water consumed by humans will play a major role in people's lives. This study used a cross-sectional design and the sample used in this study used total sampling. The total sample size was 30 respondents. Data were collected by questionnaire to determine the relationship between knowledge, attitude, and action of the community with the microbiological quality of borehole water. Samples of clean water and drinking water were taken to determine the microbiological quality of water. Data were analyzed using the chi-square test. Based on the results of the chi-square test, there was no relationship between knowledge and attitude with the microbiological quality of borehole water, and there was a relationship between action and microbiological quality of borehole water with a p-value of 0.001. Proper action in the management of borehole water could reduce the risk of microbiological pollution. These findings were expected to be the basis for efforts to improve the quality of clean water in the neighborhood around the landfill and provide useful information for the community and related parties in maintaining environmental health.